Nutritional quality evaluation of plant-based elementary school meals in Seoul - Kim, So-Young; Kim, Meeyoung (Nutrition research and practice, 2025)
This study aimed to assess the nutritional quality of plant-based school meals by comparing plant-based and regular menus in Seoul's elementary schools. Nutrient information for plant-based and regular menus (Monday-Friday) was collected from school websites during a designated week in June 2023 when plant-based meals were offered. The analysis included 1,526 menus (321 plant-based, 1,205 regular) from 313 of 608 schools. Average energy and nutrient content were calculated for both menu types, along with the proportion of schools meeting the nutritional standards for school meals provided by the Ministry of Education in South Korea. Statistical analyses included χ tests, Fisher's exact test, and -tests (α = 0.05). Analysis of energy and nutrient content in both menu types revealed that all nutrients, except vitamin C, met or exceeded the nutritional standards for school meals. However, plant-based menus provided significantly lower levels of energy, protein, fat, thiamine, and vitamin C, and higher levels of carbohydrates, calcium, and iron compared to regular menus. While the macronutrient energy distributions of both menu types were within recommended ranges, plant-based menus tended to have higher carbohydrate ratios and lower protein and fat ratios. Furthermore, schools were more likely to serve plant-based menus that fell short of the nutritional standards for several nutrients. Some plant-based menus were identified as nutritionally unbalanced, revealing fundamental shortcomings in menu design-particularly an overreliance on carbohydrate- and fat-rich foods as staples, side dishes, and desserts, as well as frequent use of oil-based cooking methods. Overall, these findings suggest a need for review and re-examination of the nutritional aspects of plant-based menus currently served in Seoul's elementary school meals.